Detecting Different Concentrations of Potassium Chloride Using the Sensor with Photonic Crystal in Nano Range - J Patil, Harshada; T S2, Indumathi; Sharan, Preeta (International Journal of Engineering and Technology, 2018)
SensitivityÂ scheme with sensing and evaluating chemicals have beenÂ clued-up by means of photonic sensors by coalescing chemical constituents with their optophysical properties. In this article we have corroborated a 2D ring resonator using photonic crystal optical sensor which can detect potassium chloride by knowing the transmitted flux. According to the corresponding analogyÂ peaks were explored. Yeeâ€™s method has been used for the assessment. ElectromagneticÂ 2D model implemented to do the initiationÂ all pass ring resonator photonic crystal. TheÂ different concentrations of potassium chloride respectively shifts its values with the respected frequency used in the design. The quality factor from the sensor is found to beÂ 347663 and the sensitivity included is found to be in the range of 1.2 NM. The distinction in the minor level of the refractive indexÂ occur the alteration for the cause in the judicious forming the frequency that is obtained by observing the simulation. These technique that is used toÂ authorize the design which isÂ unequivocally an active sensors. This analogy of the paper was been made using theÂ deliberatedÂ Â IPKISSIMEC tool. The GDSII file was generated with the OWL VISION tool andÂ substantiated meticulously using the tool K-Layout . The ASCII code was formed using the generatedÂ OWLVISION tool.Â Â Â